FGF-21 as a Potential Biomarker for Mitochondrial Diseases - Scholle, Leila M.; Lehmann, Diana; Deschauer, Marcus; Kraya, Torsten; Zierz, Stephan (Current Medicinal Chemistry, 2018)
The diagnosis of mitochondrial diseases is still challenging due to clinical and genetical heterogeneity. The development of advanced technologies including Whole-Exome- Sequencing (WES) and Whole-Genome-Sequencing (WGS) has led to improvements in genetic diagnosis. However, a reliable biomarker in serum could enhance and ease the diagnosis and indeed reduce the need for muscle biopsy. Several studies suggest Fibroblast growth factor 21 (FGF-21) as a biomarker for diagnosis in mitochondrial disorders. It is known, that in patients with mitochondrial disorders, the expression of FGF-21 gets elevated in an effort to counteract the underlying metabolic deficiency. The growth and differentiation factor 15 (GDF-15) has been described as a potential biomarker for mitochondrial diseases, too. In the present review, a literature research, using PubMed database about the reliability of FGF-21 as a biomarker for mitochondrial disorders and its comparison with GDF-15 has been performed.
Keywords: biomarker